(untitled) - Frey, David (San Francisco, 2003)
Updated for the newest releases of Autodesk's market -leading computer-aided design products, AutoCAD X and AutoCAD X LT, this book provides a thorough introduction to the essentials by using step-by-step instructions and hands-on projects. By the end of the book you will have designed a complete summer cabin. Information is also geared toward the interests of mechanical and civil engineers. You will enjoy the concise explanations and examples of vital features and tools without a lot of unnecessary discussion. Written for AutoCAD novices, it will prepare you to delve into the more advanced topics and projects covered in George Omura's Mastering AutoCAD.
Keywords: Computer graphics,Computer-aided design,Thiết kế hỗ trợ máy tính,Đồ họa máy tính